Investment Decisions Among Young Investors: Mediating Role of Risk Perception and Risk Tolerance in Relationship Emotional Intelligence and Financial Literacy - Siti Aisjah; Atim Djazuli; Cicik Retno Wati; Muhammad Fajrul Islam F; Wildan Fadhila; Nuraini Desty Nurmasari (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2026)
This study investigates the influence of financial literacy and emotional intelligence on investment decisions among Generation Z in East Java, considering the mediating roles of risk perception and risk tolerance. Employing a quantitative approach, data were collected from 500 respondents aged 18–24 with valid single investor identification (SID) and prior capital market investment experience. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that financial literacy significantly affects investment decisions, risk perception, and risk tolerance; however, its indirect influence through risk perception and tolerance is not significant. Conversely, emotional intelligence has a direct and significant effect on investment decisions and also indirectly influences them through both mediating variables. These results underscore the importance of integrating emotional intelligence and risk management training into financial education programs targeting young investors. This research highlights the psychological dimensions of financial decision-making and provides practical insights for policymakers, educators, and financial institutions seeking to promote more informed and sustainable investment behavior.